Knowledge, attitudes and perception of people from Konzere village in Chikwawa towards HIV and AIDS in relation to death cleansing. - Changadeya, Maclean Lapsone (Kamuzu University of Health Sciences, 2022)
The aim of the study was to asses the knowledge, attitude and perception of the people from Konzere village in Chikwawa on HIV and AIDS in relation to Death cleansing. The study also assessed their source of information on HIV and AIDS. The study was conducted using qualitative design and a purposive sampling on key informants and those who were convenient was used to select participants. A depth structured interview guide was used to collect data from the participants who were fourteen in total. The interview guide was in two versions; English and Chichewa. The data was analysed manually to identify prominent themes. A letter to seek permission to conduct this research was sent to Kamuzu College of Nursing Research Committee and the village Head man. The participants were fully notified of the study and were told to participate freely and with draw from the study at any point without being punished. The study found out that the people from Konzere community were aware about HIV and AIDS but they lacked comprehensive knowledge on HIV and AIDS. The findings of the study had also shown that the people from Konzere community were knowledgeable about the dangers of death cleansing in the light of HIV and AIDS considering the fact that condom use is not allowed during the death cleansing ritual. Despite all this knowledge, the ritual is still continued by the people in the area due to the cultural believes and values that are deeply rooted to each member of the community since the information about death cleansing is passed to each generation while it is still young.